Science and Policy to Meet at 2013 AGU Conference. (2nd April 2013) - Uhlenbrock, Kristan
Abstract : On 24–26 June, hundreds of leading scientists, policy makers, industry professionals, and other interested stakeholders will join together at AGU's second annual Science Policy Conference in Washington, D. C. The theme for the 2013 conference, "Preparing for Our Future, " serves as a discussion point on how the Earth and space sciences can better prepare communities for a changing climate, support the national economy through innovative science, and protect the health and safety of humans and the environment around the globe.